SUITABILITY OF SAGO STARCH BLENDED WITH ACRYLAMIDE AS AN ADDITIVE ON HANDSHEETS MADE FROM RECYCLED PULP FIBERS - Wong Sin Yeng; Paridah Md. Tahir; Liew Kang Chiang (ASEAN Journal on Science and Technology for Development, 2005)
This study was carried out to determine the suitability of sago starch blended with acrylamide as paper additive. Solutions of unmodified and blended sago starch with acrylamide, were prepared at 5% weight over volume (w/v) basis before the basic properties (i.e., pH, viscosity and solid content) were determined. Thestarches were thenused to coat on laboratory made handsheets from recycled pulps. Various effects were studied, namely, modification of sago starch, addition of different types of initiator and further curing at different temperatures. The incorporation of acrylamide into sago starch through blending signif icantly increased the pH and viscosity of the solutions. All the blended starches remained biologically resistant even after 14 days of exposure to ambient temperature. Solutionof sago starch blended with acrylamide, gave superior performance when coated on the handsheets, producing handsheets with high folding endurance (110 times) and crushstrength (128 N) ascompared to the handsheets coated with the unmodified sago starch. Nevertheless, the smoothness and air permeance of these papers were unsatisfactory due to insufficient curing shown by the micrographs. The use of ceric ammonium nitrate (CAN) as initiator and further curing at 50oC however, were able to improve the smoothness and air permeance properties.